Failure recovery algorithm for LRT and transaction property analysis - Xiao-yong MEI; Chang-qin HUANG; Xiao-lin ZHENG; De-ren CHEN; Shi-xian LI (Tongxin xuebao)
Researchers have worked on recovery strategies of composition transactions,most efforts focus on transaction consistency by backward recovery,compensation is commonly used for backward recovery,which have limitations since the cost of compensation tasks are rather expensive,and the compensation mechanism can not satisfy various requirements of applications.A transaction recovery algorithm was proposed including forward recovery,backward recovery and alternative recovery,which was a formal modeling method based on extended Petri nets,state token，data token and QoS token were introduced to implement relaxed ACID properties of LRT.When failure occurs,terminate dependency point (TDP) and compensation set were calculated dynamically,recovery strategies were added or deleted automatically according to the data flow dependency,control flow dependency and state dependency among tasks.Failure types are generated by log file mining,therefore,failure coordination and recovery are implemented and an executable model which support add/delete failure recovery behavior is constructed seamlessly.